LEXICAL DIFFICULTIES IN THE ELDERLY. BASIS FOR INTERVENTION - Juncos Rabadán, Onésimo; Elosúa de Juan, María Rosa; Pereiro Rozas, Arturo; Torres Maroño, María del Carmen (Anales de Psicología / Annals of Psychology, 1998)
We analyse lexical access according to a processing model in two phases: 1) semantic, in which an independent representation of meaning or pre-phonological unit (lemma) is selected, and 2) phonological, in which the spared knowledge of lexical form (lexema) is available. The model works with two main mechanisms: transmission across semantic and phonological representations and activation-inhibition that allows retrieval of the target unit and blocks other alternates in competition with the target. In the light of this model, results obtained by Juncos and Iglesias (1994) from their translinguistic study with 840 subjects speaking fourteen different languages and distributed in three groups of age (50-59; 60-69; and over 70 years) are interpreted. We consider the subjects’ performances in the following Subtests of the Bilingual Aphasia Test (Paradis, 1987): Semantic Categories, Synonyms, Antonyms, Semantic Acceptability, Lexical Decision, Verbal Fluency, Semantic Opposites, and Reading Comprehension of Words. The results did not show significant differences among age groups on Semantics Categories and Semantic Acceptability Subtests. From those results we interpret old people to have no difficulty in the organisation of semantic fields and therefore age has not negative effects on conceptual and semantic knowledge. Older individuals have no problems in lexical decision and verbal fluency tasks, showing a good organisation of the Phonologically Lexicon. The older adults obtained poorer rates than the young adults on Synonyms, Antonyms and Semantic Opposites Subtests. Their difficulties could be due to a breakdown on the access to the Phonological Lexicon from the Semantic Lexicon. This breakdown could be interpret as a deficit in the connection between the two systems or as a deficit in the competition of possible alternates.